Determination of fluoride in black, green and herbal teas by ionselective electrode using a standard-addition method - Mochammad Yuwono (Dental Journal (Majalah Kedokteran Gigi), 2005)
Tea leaves are very rich in fluoride, since tea plants take up fluoride from the soil and accumulate in its leaves. Some of this fluoride is released into the infusion, which is drunk as tea. Fluoride in tea could be beneficial for the prevention of dental caries, but it may result in excessive intake and lead to enamel fluorosis. The purpose of this work was to determine the fluoride levels in 12 different brands and types of tea by means of a computer-controlled ion-selective electrode potentiometry using a standard-addition method. It is a rapid method which showed good accuracy and precision. Fluoride contents of tea infusions after 5 min ranged from 0.95 to 4.73 mg/l for black teas; from 0.70 to 1.00 mg/l for green teas, and from 0.26 to 0.27 mg/l for herbal teas. It was concluded that black teas and green teas examined may be important contributors to the total daily fluoride intake. However, the ingestion of some black teas that were found to have high fluoride content by children at the age of risk to dental fluorosis should be avoided.